2018
DOI: 10.21608/agro.2018.6277.1134
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Cropping System and Integrated Nutrient Management on Nutrients Uptake and Utilization by Maize Grown in Calcareous Soil

Abstract: Inroduction Recently, much higher nutrient outflows due to some bad practices followed by farmer's viz., intensive agriculture, neglected cropping sequences and ignored fertilization programs; all these among the factors of soil degradation are the main challenges facing improving agriculture. Thus, low priority is given to increasing the current productivity to meet the present rapid population growth and changing in food preferences, as well as decreasing the gap between total food production and human consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…We can also interpret that the integrated application of organic and inorganic nutrient showed highest yield compared to all other inorganic and organic treatments. The result previously supported by many researchers indicated that INM practice can be an effective practice and eco-friendly approach to produce greater yield production and maintain satisfactory stable profitability to farmers (Selim, 2018;Parmar and Sharma, 2002;Cheuk et al, 2003;Sarwar et al, 2007;Sarwar et al, 2008;Abedi et al, 2010;Ghosh et al, 2010;Diacono and Montemurro, 2011). Whereas among all the organic treatment 33% of recommended N each from FYM, vermicompost and Neem cake along with Azospirillum, Azotobacter, Rhizobium and PSB (T5) showed highest yield in all the cropping system.…”
Section: Crop Yield and System Yieldmentioning
confidence: 81%
“…We can also interpret that the integrated application of organic and inorganic nutrient showed highest yield compared to all other inorganic and organic treatments. The result previously supported by many researchers indicated that INM practice can be an effective practice and eco-friendly approach to produce greater yield production and maintain satisfactory stable profitability to farmers (Selim, 2018;Parmar and Sharma, 2002;Cheuk et al, 2003;Sarwar et al, 2007;Sarwar et al, 2008;Abedi et al, 2010;Ghosh et al, 2010;Diacono and Montemurro, 2011). Whereas among all the organic treatment 33% of recommended N each from FYM, vermicompost and Neem cake along with Azospirillum, Azotobacter, Rhizobium and PSB (T5) showed highest yield in all the cropping system.…”
Section: Crop Yield and System Yieldmentioning
confidence: 81%
“…In addition, it can match the crop nutrient requirements and alleviate the constraints of nutrient deficiency without any harmful effects in the environment and products. In contrary, in the case of mismanagement, it always leads to soil degradation, nutrient deficiency, and quick soil runoff [7].…”
Section: Introductionmentioning
confidence: 99%
“…Since ancient times, farmers have known that soil health can be restored by applying organic manure; accordingly, they used to apply farmyard manure regularly and directly after crop harvest. Consequently, the custom of using organic manures after harvesting has been coupled with restoration of soil health and improvement of physical, chemical, and biological properties of soil, particularly in marginal soils, which are already suffering from low organic matter and low native nutrient content, low productivity, and limitations and unavailability of essential nutrients [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations